Implementasi Fungsi Manajemen Dakwah DPD BKPRMI dalam Mengantisipasi Tawuran Antar Remaja Dikota Rantau Prapat - Ihsan Almunawwar Siregar; Soiman Soiman (Dinasti Review, 2024)
Implementation of the Da'wah Management function carried out by the Regional Management Council (DPD) of the Indonesian Mosque Youth Youth Communication Agency (BKPRMI) in anticipating brawls between teenagers in the city of Rantau Prapat. This type of research uses qualitative methods. Data collection techniques through observation, interviews and documentation studies. The results of the research found that the DPD BKPRMI organization carries out activities and programs of activities carried out by the Dakwah Routine training through tausiyah as well as friendship with all the youth of the target mosque which is carried out every month and various activities carried out by the youth are carried out through Islamic study activities regarding materials. . Da'wah, religious modification, counseling and commemoration of the Islamic Biesar Day (PHBI), piengkadieran and social service, siepierti festival for sholieh children. Due to the da'wah activity carried out by the BKPRMI organization, Tiersie said it was to anticipate brawls between young people in Rantau Prapat City. This organization has a great influence on young people to have a good impact on young people in developing knowledge and formation of positive morals and behavior and young people to anticipate brawls between teenagers in the environment around Rantau Prapat City.